If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -2 = 30y + 3 Reorder the terms: -2 + 15y = 30y + 3 Reorder the terms: -2 + 15y = 3 + 30y Solving -2 + 15y = 3 + 30y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-30y' to each side of the equation. -2 + 15y + -30y = 3 + 30y + -30y Combine like terms: 15y + -30y = -15y -2 + -15y = 3 + 30y + -30y Combine like terms: 30y + -30y = 0 -2 + -15y = 3 + 0 -2 + -15y = 3 Add '2' to each side of the equation. -2 + 2 + -15y = 3 + 2 Combine like terms: -2 + 2 = 0 0 + -15y = 3 + 2 -15y = 3 + 2 Combine like terms: 3 + 2 = 5 -15y = 5 Divide each side by '-15'. y = -0.3333333333 Simplifying y = -0.3333333333
| 4x^2+14x=12x-5 | | 18=-8x | | 59x= | | t(20)=104.8 | | 4y^2+36=27 | | 7x+10=39 | | 22+7x=42+15x | | x(20)=104.8 | | 15=10-n | | 3x^2=24x-20 | | 6(5-8v)=-66 | | X+(X*0.09)+(X*0.05)=50000 | | 3c+(c+2)=13(2c-5) | | 6y+5=21 | | (4-i)-(6-3i)= | | 6d+22d+12=0 | | 3056890000-15000000x=2085000000+55000000x | | .50n=17 | | 10x+6=6x+7 | | 4x-10=5x-20 | | 16y+11y^2=12 | | 4(x+2)-3=2x+1 | | 5-3(4-2b)=4(b-3) | | 19-20b=18 | | 3x-(x+1)=41 | | 16n=5n | | 5x-12=4-6x | | -2(-3x)=8x+2x | | -37=3-8x | | 19x=49-10 | | 6x-4-3x=20 | | (3a+7)(2a-5)= |